Think, Check & Submit: Unique Approach to Journal Selection - Md Ashif Iqbal (Update Dental College, 2022)
In recent decades, the fast transition from print to digital publishing has resulted in an unparalleled increase in scholarly journal publications. The wide range of options accessible to them is increasingly overwhelming to many academics, particularly early-career scholars, researchers, or faculty members of an institution online. Researchers questioned following their findings, "Where should I publish my article for others to read?" In science, the answer to this issue has never been trivial, but it is today more crucial than ever. How can you, as a researcher, determine whether the publication you are going to submit your research to is legitimate? Think. Check. Submit, a campaign by a consortium of scholarly communications groups, may hold the key to finding the solution. Think, Check, and Submit is a tool that facilitates the process of selecting the best journal for your research publication. It is getting harder and harder to choose which academic publication is worthy of your work with the release of hundreds of new academic online journals every year. Although having more options is typically a good thing, the profusion of new titles has also led to a rise in what some refer to as "predatory publishing." Update Dent. Coll. j: 2022; 12(2): 1-2